ANALISA MATERIAL CRYSTALINE SILICON WAFER SOLAR CELL DENGAN MENGGUNAKAN TYPE DRY MACHINES - La Hasanudin; Al Ichlas Imran; Agustinus Lolok; Aminur Aminur (Dinamika : Jurnal Ilmiah Teknik Mesin, 2019)
The Photovoltaic (PV) industry is one of the renewable energy segments, and electricity generation from photovoltaics (solar cells) is considered one of the key technologies of the century in the future. Photovoltaic solar electricity presents an elegant way to generate electricity, because there are no movements that damage the environment, namely: zero emissions, and no noise. This study aims to determine the efficiency analysis of making Crystaline Silicon by using type dry machines. The method that is carried out is the manufacture of Crystanesilicon by using type Dry machines. Produce nano wire devices that provide efficiency above 5%, with short photocurrent circuits higher than planar control samples. Thickness The thickness of the Si wafer depends on its diameter for reasons of mechanical stability during production and further processing, and about 279 μm (for wafers in diameter 2 inches), 379.5 μm (3 inches), 524.5 μm (4 inches), 674.5 μm (6 inches) and 724.5 μm (8 inches).